POPULATION PARAMETER AND REPRODUCTIVE BIOLOGY OF INDIAN MACKEREL Rastrelliger kanagurta (Cuvier, 1817) CAUGHT BY LIFT NET IN KWANDANG WATERS, NORTH GORONTALO - Ria Faizah; Lilis Sadiyah; Moh. Fauzi (Research Center for Fisheries, 2017)
Kwandang waters is one of the main base for small pelagic fisheries in Sulawesi sea in which the Indian mackerel (Rastrelliger kanagurta) has been exploited. The objective of the research was to estimate the population parameters, exploitation rate and reproductive biology of Indian mackerel. Length frequency data were collected from PP Kwandang, between February and October 2012. Estimation of population parameters of Indian mackerel was done using FISAT II method. The results showed that growth rate as follows (K) = 0,80 year-1 , L∞=27,3 cm. Total mortality rate (Z) = 2,72 year-1, with natural mortality (M) = 1,29 year-1 and fishing mortality (F) = 1,43 year-1 and exploitation rate (E)=0,53. Exploitation of Indian mackerel in Kwandang waters have reached its optimum level. The sex ratio of Indian mackerel was balance. The most commonly found is Gonado Maturity Stage of I. Based on the results, it is necessary to manage with the responsible management through gradually increasing of the mesh size of the gears or restricting additional lift net or by restricting fishing for certain seasons or declaring fish sanctuaries in certain areas, especially in spawning grounds to protect the Indian mackerel.